2010
DOI: 10.1590/s0100-204x2010000700011
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros genéticos de caracteres agronômicos em genótipos de mamoneira

Abstract: O objetivo deste trabalho foi avaliar os parâmetros genéticos de caracteres agronômicos, em populações fixas e segregantes de mamoneira (Ricinus communis). Os experimentos foram conduzidos entre 2006 e 2009, com populações fixas e segregantes obtidas de cruzamentos entre as cultivares BRS 149 Nordestina, BRS 188 Paraguaçu, EBDA MPA 17, Mirante 10 e Sipeal 28. Os caracteres avaliados foram: estatura de planta (EST), número de dias do plantio ao florescimento (FLO), número de frutos de três racemos (NFR), número… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
(3 reference statements)
1
7
0
1
Order By: Relevance
“…PASSOS et al (2010) reported the heritability for this character as being 28%, 47%, 69% and 38%, in the fixed and segregant populations of crosses of different castor bean cultivars. DA SILVA et al (2011) in their study characterizing the cashew cultivars indicated for cultivation in South Brazil confirmed the heritability for this character as 25%; they indicated that the environmental conditions of temperature, sufficient precipitation and fertilization can support plant growth, whereas the unfavorable conditions could induce losses in this character.…”
Section: Resultsmentioning
confidence: 99%
“…PASSOS et al (2010) reported the heritability for this character as being 28%, 47%, 69% and 38%, in the fixed and segregant populations of crosses of different castor bean cultivars. DA SILVA et al (2011) in their study characterizing the cashew cultivars indicated for cultivation in South Brazil confirmed the heritability for this character as 25%; they indicated that the environmental conditions of temperature, sufficient precipitation and fertilization can support plant growth, whereas the unfavorable conditions could induce losses in this character.…”
Section: Resultsmentioning
confidence: 99%
“…Vegetative cycle presented a value of 0.23 for broad-sense heritability. This value is considered low compared to the results obtained by PASSOS et al (2010). Those authors evaluated the vegetative cycle for crosses that originated the population under study, and reported the following values: 0.64 ('BRS 149 Northeast' × 'EBDA'); 0.38 ('BRS 149 Nordestina' × 'Sipeal 28'), 0.86 ('BRS 149 Nordestina' × 'Mirante 10') and 0.65 ('BRS 188 Paraguaçu' × 'EBDA MPA 17').…”
Section: ------------------------------------------------------------mentioning
confidence: 70%
“…The great variability among castor bean genotypes means there is a large genetic base for the creation of new strains with favorable genetic combinations. Therefore, a substantial challenge for breeders is to aggregate the highest possible frequency of desirable alleles in a single genotype (SEVERINO et al, 2006;PASSOS et al, 2010;PATEL & PATEL, 2014;SILVA et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its valid mention that, generally, in the city of Araçatuba were observed the highest estimates of heritability, indicating that besides the possibility of genetic gain with the progeny selection, this environment also favors the choice of more stable progenies, being this reasoning shared by Silva et al (2011), that observed relation between heritability and phenotypic stability face of environmental variations (Silveira et al, 2016;Passos et al, 2010). High estimates of heritability also demonstrate good genetic control, assuming that the most of the observed variation in castor bean plants was genetic in nature (Cruz Neto et al, 2016).…”
Section: Continuaçãomentioning
confidence: 86%